Influence of lubricant type on churning power loss of worm gear - Hardik G. Chothani; Devendra J. Marsonia; Nisha N. Jadeja; Sanjay H. Zala; Ketan S. Vaghosi (Tribology and Materials)
This paper presents the results of experimental tests of the churning power loss of a single-stage worm gear. The churning power loss is a load-independent loss that occurs when the gear churns through the lubricant. This study will solely look at how churning power losses are affected by mineral and synthetic oil on a test worm gear pair where the worm shaft is made of 16MnCr5 and the worm wheel is made of CuSn12. As a lubricant, mineral and synthetic oil were used for gears operating at variable speeds, different oil volumes and positions of the worm shaft. The direct torque measurement method was used in a thorough experimental investigation. A new test rig was devised, built and put into service to quantify churning power loss in unloaded situations. According to the experiment results, churning power loss values for mineral oil are 20 – 25 % greater than those of synthetic oil, which has almost the same kinematic viscosity at a temperature of 40 °C.